Knowledge and Practice of Hepatitis B Virus Infection Prevention among Young Adults in Benue North-East: A Cross-Sectional Study - Zwawua, Orfega; Ukpekeh, Smith Tertsegha; Ityodugh, John Ityonande (Insights in Public Health Journal, 2024)
ABSTRACT Backgound: The increasing prevalence of HBV infection in Benue State, especially among young adults has called for public health concern. This study, therefore, assessed knowledge and practice of HBV infection prevention among young adults (18 – 35 years) in North-East Senatorial District of Benue State, Nigeria. Methods: A cross-sectional resesrch design was used, and a sample size of 440 was drawn from a population of 404,270 young adults. A researcher-developed questionnaire (KAP-HBVIPQ) with reliability coefficients of 0.85 and 0.74 for knowledge and practice, respectively, was used for data collection. Descriptive statistics were used to describe sociodemographic characterisics and to analyse responses on knowledge and practice items. Pearson chi-square statistics was used to test for association between knowledge/practice of HBV infection prevention and sociodemographic characteristics. Significant associations were declared at P < .05. Results: The overall knowledge regarding HBV infection prevention was poor as more than half (53.6%) of the participants scored below 50% on knowledge items. Practice of HBV infection prevention was fair as almost half (49.9%) of the participants scored from 50 – 69% on practice items. Good knowledge/practice of HBV infection prevention was significantly associated with being a female, being of older age (30 – 35 years), acquiring tertiary education,and having a family member infected with HBV (P < .05). Conclusion: Young adults’ knowledge of HBV infection prevention was poor, while their practice was fair but not encouraging. Therefore, the Benue State Government in collaboration with Local Government Authorities and NGOs in Benue North-East should step up public health education activities on HBV infection prevention, targeting mostly young adults with no or low level of education.